nm23 as a prognostic marker in primary cutaneous melanoma: evaluation using tissue microarray in a patient group with long-term follow-up. - Pacifico, MD; Grover, R; Richman, P; Buffa, F; Daley, F; Wilson, G (2005)
The accurate estimation of prognosis in patients with melanoma is of increasing importance with novel adjuvant therapies on the horizon. The current prediction of prognosis employs techniques involving sentinel lymph node biopsy, which carries an associated morbidity and is of little use in patients who develop direct distant metastases or direct in-transit metastases. New strategies or factors are therefore needed to improve the accuracy of determination of prognosis. nm23 is a putative metastasis suppressor; however, conflicting data exist as to its role in melanoma progression and its use as a potential prognostic marker. The purpose of this study was to use the technique of tissue microarray to study a cohort of melanoma patients with long-term follow-up data in order to ascertain its potential use as a prognostic marker. One hundred and twenty patients with primary cutaneous melanoma were included in the tissue microarray and a commercially available immunohistochemical marker for nm23 was used for protein detection. nm23 expression was strongly correlated with Clark's level (P<0.001), Breslow depth (P=0.002) and patient age (P=0.014). nm23 expression was significantly associated with a poor patient outcome (chi2=7.2219, P=0.0072). Further analysis revealed that the intensity of nm23 expression also correlated with patient outcome (chi2=11.3281, P=0.0035). However, on multivariate analysis, nm23 was shown not to be an independent marker of prognosis. The results of this study, when taken with the existing literature, suggest a role for nm23 in melanoma disease progression. However, its use as a prognostic marker in routine practice does not appear to be justified.